2020
DOI: 10.1186/s40780-020-00159-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hypoglycemia associated with repaglinide combined with clopidogrel, a retrospective cohort study

Abstract: Background: Repaglinide is widely prescribed to reduce postprandial hyperglycemia and elevated glycated hemoglobin (HbA1c) levels associated with type 2 diabetes, and clopidogrel is a thienopyridine antiplatelet agent and widely used in cardiovascular and cerebrovascular diseases. It has been suggested that the concomitant use of repaglinide with clopidogrel may inhibit repaglinide metabolism, because repaglinide is a substrate of cytochrome P450 2C8 (CYP2C8) and the main metabolite of clopidogrel acyl-β-D-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Considering that the patient had mild anemia, probably because of severe renal insufficiency, and her actual HbA1c value was assumed to be slightly higher than the measured value (6.4%), we believe that our patient's condition was adequately controlled. It has recently been reported that the concomitant use of repaglinide and clopidogrel causes hypoglycemia in patients with T2DM (7,8). Wei et al reported that the concomitant use of repaglinide and clopidogrel was associated with an increased risk of hypoglycemia compared with repaglinide alone in a population-based study using real-world data in Taiwan (adjusted odds ratio: 2.42; 95% confidence interval: 1.75, 3.35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering that the patient had mild anemia, probably because of severe renal insufficiency, and her actual HbA1c value was assumed to be slightly higher than the measured value (6.4%), we believe that our patient's condition was adequately controlled. It has recently been reported that the concomitant use of repaglinide and clopidogrel causes hypoglycemia in patients with T2DM (7,8). Wei et al reported that the concomitant use of repaglinide and clopidogrel was associated with an increased risk of hypoglycemia compared with repaglinide alone in a population-based study using real-world data in Taiwan (adjusted odds ratio: 2.42; 95% confidence interval: 1.75, 3.35).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that the concomitant use of repaglinide and clopidogrel causes hypoglycemia in patients with T2DM ( 7 , 8 ). Wei et al reported that the concomitant use of repaglinide and clopidogrel was associated with an increased risk of hypoglycemia compared with repaglinide alone in a population-based study using real-world data in Taiwan (adjusted odds ratio: 2.42; 95% confidence interval: 1.75, 3.35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood samples were gained following overnight fasting to measure total cholesterol and serum glucose. Hypoglycemia was defined as a plasma glucose level less than 70 mg/dL 23 . Comorbidities were estimated by screening before index date using medical records, and the comorbidities were composed of dyslipidemia (ICD‐10: E78), hypertension (ICD‐10: I10‐I15), chronic kidney disease (ICD‐10: N18), ischemic heart disease (ICD‐10: I20‐I25), stroke (ICD‐10: I60‐I63), cancer (ICD‐10: C00‐C99), and depressive disorders (ICD‐10: F32‐F33).…”
Section: Methodsmentioning
confidence: 99%